Rom, Italien: Der Bestand „Paul des Granges“ an der Fotothek des DAI Rom - Pasieka, Paul P. (e-Forschungsberichte des DAI, 2023)
The collection Paul des Granges, consisting of approximately 200 negatives and spanning the years between 1865 and 1880, is one of the oldest photographical collections currently preserved at the photographical archive of the DAI Rome. The aim of the project is both a systematic exploration of the collection as well as a reconstruction and contextualisation of the life and work of Paul des Granges by the means of an accompanying archival and bibliographical research. Paul des Granges was not only a pioneer of photography at the beginning of the second half of the 19th century but he also had a vast personal, pan-European network at his disposal. Although emphatically praised by his contemporaries, he was almost forgotten at the end of the 19th century.